Green tea and type 2 diabetes - Park, Jae-Hyung (Integr Med Res, 2014)
Green tea and coffee consumption have been widely popular worldwide. These beverages contain caffeine to activate the central nervous system by adenosine receptor blockade, and due to the caffeine, addiction or tolerance may occur. In addition to this caffeine effect, green tea and coffee consumption have always been at the center of discussions about human health, disease, and longevity. In particular, green tea catechins are involved in many biological activities such as antioxidation and modulation of various cellular lipid and proteins. Thus, they are beneficial against degenerative diseases, including obesity, cancer, cardiovascular diseases, and various inflammatory diseases. Some reports also suggest that daily consumption of tea catechins may help in controlling type 2 diabetes. However, other studies have reported that chronic consumption of green tea may result in hepatic failure, neuronal damage, and exacerbation of diabetes, suggesting that interindividual variations in the green tea effect are large. This review will focus on the effect of green tea catechins extracted from the Camellia sinensis plant on type 2 diabetes and obesity, and the possible mechanistic explanation for the experimental results mainly from our laboratory. It is hoped that green tea can be consumed in a suitable manner as a supplement to prevent the development of type 2 diabetes and obesity.